Assessing Thailand's international competitiveness: A generalised double-diamond approach - Wongsawat, Natjarate (Auckland University of Technology, 2005)
The Thai economy has been enjoying impressive growth following the financial crisis in 1997. Despite this recovery, Thailand’s competitiveness in recent years has stagnated. Other additional issues have also caused concerns over the future of Thai competitiveness and raised important questions. Whether Thailand can continue relying on its lower-cost labour and other fundamental advantages as keys to sustained economic growth and competitiveness remains vague. Hence, a study examining and assessing Thai competitiveness is timely in order to provide insights in this area and to draw out effective policies for sustained competitiveness development. Thai research into this area remains undeveloped with a distinct lack of in-depth analyses. Porter’s (2003) research appears to be the only serious study that provides theoretical findings and policy recommendations to enhance Thai competitiveness. However, the weaknesses of the Porter model (1990) have caused scepticism about the reliability and accuracy of the findings. Therefore, this dissertation applies a more rigorous and advanced framework, the generalised double-diamond model (Moon, Rugman & Verbeke, 1998) to assess and analyse Thailand’s international competitiveness. The study aims to provide theoretical findings as well as additional insights into Thai competitiveness further to Porter and to draw out reliable policy recommendations. As the generalised double-diamond framework integrates international variables with Porter’s domestic diamond model, the research findings provide a more comprehensive picture of Thai competitiveness performance. While producing evidence to support Porter’s (2003) findings, the study also offers additional insights to better understand Thai competitiveness. This is especially obvious in the area of the international determinants of competitiveness that Porter failed to investigate, such as international demand conditions and international related and supporting industries. Finally, the study suggests more specific policies that directly improve the main problems of Thai competitiveness further to those suggested by Porter (2003). These additional policies should receive more attention from the government, firms and policymakers to reinforce Thai competitiveness and enable Thailand to compete more effectively with other nations around the globe.
Keywords: Competition; International -- Thailand